The treatment [videorecording (DVD)] - Herbots, Hans, 1970-; Van Rampelberg, Geert; Geerts, Ina; Assche, Johan van, 1956-; Hayder, Mo (Artsploitation Films, 2015)
"Based on the international bestselling novel by British crime writer Mo Hayder, The Treatment is a gripping, unsettling story. A police inspector is assigned a case where a mother and father have been bound and beaten, and their young son is missing. As he investigates, the troubled cop uncovers other similar cases including a repressed episode from his own childhood. Grim and wholly engrossing, The Treatment is a dark, disturbing thriller with an edge"--Container.